Students’ Perceptions of Its Usefulness and Ease of Use on Learning Management System - Linda Khoo Mei, Sui; Nurlisa, Loke Abdullah; Subatira, Balakrishnan; Wan Sofiah, Meor Osman (The Science and Information Organization (SAI), 2024)
Abstract: The importance of the Learning Management System (LMS) has been discussed over recent years as it is crucial for students to manage this tool for their learning. The study's objective was to ascertain whether learners believe the LMS satisfies their learning goals and to bridge the gap between the growing body of research on learner-centered instructional design and LMS design. A survey was carried out with 528 students to get the data. The results revealed that most of the learners agreed that LMS is a useful tool to enhance their learning. This proves that LMS can be used as a device to make their learning better and more effective. The study's conclusions could be used as a guide for the university's administration as it adopted pertinent digital technologies, with the goal of creating an efficient implementation strategy that would enhance service delivery. Universities and colleges would benefit from this established approach in selecting the best learning management system (LMS) to meet their diverse needs. It will also act as a guide for developers who want to create an assessment system.